Otimizando as redes de distribuição de gás natural : Um resumo do estado da arte de projetos mundiais e Brasileiros usando o biometano e hidrogênio - Meloni Massara, Vanessa; Morales Udaeta, Miguel Edgar; Veiga Gimenes, André Luiz (Latin American Journal of Energy Research, 2025)
Aiming for the energy transition, Brazil, like the entire World, intends to make its energy matrix cleaner. This Paper addresses, how the issue of using already consolidated natural gas infrastructure can be adapted to a combination with hydrogen, in the specific case of Brazil, first, through the use of natural gas combined with biomethane. To this end, a bibliographical review of existing projects in the World and Brazil is carried out. The conclusion is that, in the Brazilian case, given the requirement of the law, the injection of hydrogen by 2025 will be 5% and by 2050, 10%, using an existing natural gas network, but, beginning with the and requiring a technical review of the condition of this infrastructure for this purpose.